Empowering Rural Women in Indian Agriculture throughICT - Arvind Kumar,; Sunil Kumar,; Aman Verma,; Saba Siddiqui,; Naresh Babu,; Ajeet Kumar Bajpai,; Mustafa Hussain, (The Bioscan, 2026)
The present study examines the increasing significance of Information and Communication Technology (ICT) in rural India, with particular emphasis on its tools, applications, and contribution to empowering rural women engaged in agriculture. ICT tools such as mobile phones, basic communication networks, and digital platforms have emerged as accessible and practical sources of information for rural women farmers. These technologies enable them to receive agricultural advisories, technical updates, and essential messages directly, reducing reliance on traditional extension services.In recent years, services such as online banking, digital governance, e-markets, and distance-learning platforms have helped overcome long-standing challenges related to geographical isolation and social constraints in rural areasICT-based extension services have further improved the dissemination of agricultural knowledge. Mobile-based advisories, online platforms, and digital applications have enhanced farm productivity and created new income-generating opportunities for rural families. Although traditional media such as radio and television continue to play a role, India has increasingly promoted ICT-enabled agricultural initiatives, including community information centers at the village level.Despite these advancements, the adoption of ICT remains uneven across regions. Economically and technologically advanced areas benefit more from ICT integration, while less-developed regions continue to face challenges such as poor connectivity, limited infrastructure, and low digital literacy, By improving access to information and capacity-building resources, ICT helps women emerge as active contributors, innovators, and role models within the agricultural sector (Rani, 2023; Kumar & Singh, 2025). Keywords Rural Women, Agricultural Empowerment, e-Agriculture,and Expert Systems.